2017
DOI: 10.1038/s41598-017-16339-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between visual function and retinal structure in chronic central serous chorioretinopathy

Abstract: The purpose of the current study was to investigate the association between visual function and retinal structure in central serous chorioretinopathy (CSC). In 22 eyes of 22 chronic CSC patients with serous retinal detachment at the macula, retinal sensitivity was measured using MP3 microperimetry (NIDEK, Japan) and mean sensitivity within two degrees (MS2), four degrees (MS4) and six degrees (MS6), as well as foveal sensitivity (MS0), were calculated. Retinal structure was measured using optical coherence tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
(27 reference statements)
2
14
0
2
Order By: Relevance
“…Chiba et al showed that the BCVA was significantly correlated with the foveal sensitivity in macular thickening disorders [ 42 ]. Sugiura et al also reported similar results between the BCVA and macular retinal sensitivity, but this significant relationship was not observed when the retinal sensitivity was calculated from a wider retinal area in eyes with chronic CSC [ 43 ].…”
Section: Discussionmentioning
confidence: 93%
“…Chiba et al showed that the BCVA was significantly correlated with the foveal sensitivity in macular thickening disorders [ 42 ]. Sugiura et al also reported similar results between the BCVA and macular retinal sensitivity, but this significant relationship was not observed when the retinal sensitivity was calculated from a wider retinal area in eyes with chronic CSC [ 43 ].…”
Section: Discussionmentioning
confidence: 93%
“…A. Sugiura, R. Fujino, N. Takemiya не выявили наличия корреляции между центральной светочувствительностью и остротой зрения после лечения. Однако следует отметить, что авторы оценивали общую светочувствительность, которая может иметь высокие значения на периферии в зоне прилегания нейроэпителия [25]. В связи с этим в данном исследовании мы оценивали центральную фовеальную светочувствительность, измеренную в 5 точках.…”
Section: результаты и обсуждениеunclassified
“…В исследовании A. Sugiura и соавт. была установлена взаимосвязь высоты отслойки нейроэпителия с центральной светочувствительностью, но в рамках нашего исследования корреляция между этими параметрами не рассматривалась [25].…”
Section: результаты и обсуждениеunclassified
“…Most initial retinal detachments in CSC resolve spontaneously 10 , 11 ; however, chronic CSC can also be experienced where patients often complain of visual symptoms, such as decreased visual sensitivity, metamorphopsia, and central scotoma 12 14 , despite the preserved VA. Agreeing with this, we have recently shown that it was advantageous to assess the visual function in chronic CSC using the white-on-white (WW) visual field (VF) testing (with microperimetry) rather than using VA alone 15 . The retinal sensitivities, but not VA, were well associated with SRD measurements obtained by optical coherence tomography (OCT) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Agreeing with this, we have recently shown that it was advantageous to assess the visual function in chronic CSC using the white-on-white (WW) visual field (VF) testing (with microperimetry) rather than using VA alone 15 . The retinal sensitivities, but not VA, were well associated with SRD measurements obtained by optical coherence tomography (OCT) 15 .…”
Section: Introductionmentioning
confidence: 99%